Applying concepts in international relations: The language of causal explanation in high- and low-graded concept-application essays. (October 2020) - Myskow, Gordon; Underwood, Paul R.
Abstract: This paper presents findings from a systemic-functional investigation of the causal language used in high- and low-graded essays (HGEs and LGEs) in a university-level CLIL course on the topic of International Relations. The essay task-type, referred to here as the Concept Application assignment, requires writers to apply concepts, such as "Security Dilemma" or "Balance of Power", to explain a present-day or historical situation. Comparisons are made between HGEs and LGEs in frequencies of different causal resources and their realizations as well as their patterns of use in different discourse stages of the essays. Key findings include a greater reliance in high-graded essays on Abstract Causality (e.g., consequence ), resources for assessing causality (e.g., a major impact ), Internal Verbs for reasoning and drawing conclusions based on evidence ( explain, interpret ) and a coupling of Determining Relations verbs with other word classes such as modals (e.g., may cause ). Also noted was a preference in high graded essays for Internal Verb in the beginning and final stages of the essays. Pedagogical implications and suggestions for further research are discussed. Highlights: More abstract causality and causal assessments in high-graded essays ( major impact ). Preference in high-graded essays for internal verbs ( show ) to reason from evidence. Coupling of determining relations with modals ( may cause ) in high-graded essays. Greater use of internal verbs in the beginning and end stages of high graded essays. Pedagogical implications and suggestions for further research are discussed.